MORPHOMETRIC CHARACTERIZATION OF THE HYDROGRAPHIC BASIN OF JAUQUARA RIVER IN THE TRANSITION BETWEEN THE CERRADO AND AMAZON BIOMES IN MATO GROSSO-BRAZIL - Cassettari, Gabriel Americo; de Queiroz, Tadeu Miranda (Floresta, 2019)
This study aimed to perform the Jauquara river watershed morphometric characterization. To watershed delimitation was used SRTM 30 type Digital Elevation Model (Shuttle Radar Topography Mission, with spatial resolution of 30 m) provided by USGS Earth Explorer platform. The geographic information system used to watershed delimitation process and maps generation was ArcGIS 10.1 from ESRI®. The morphometric variables calculus was based on classic methodologies of Applied Hydrology. The watershed has an area of 1408,03 km2 and perimeter of 288,43 km with compactness coefficient and circularity index of Kc = 2.15 and Ic = 0.21, respectively, which show an elongated shape. The drainage was classified as 5th order, reinforcing the configuration of the drainage network with a wide hydric distribution. The predominant altitude range is between 368 and 552 m, which corresponds to an area of 478.10 km2. It was observed that there is a predominance of smooth-wavy and undulated reliefs (3-8%, 8-20% slope), which correspond to 38,05% and 23,04% of the total basin area respectively. The morphometric characterization of the basin made it possible to obtain unpublished information that contributes to the decision making regarding the effective water management in the studied area, being this a guiding study for other works